Implementation of the TGfU Learning Model in Football Learning to Improve Student Discipline Behavior - Randhi Vernanda (Journal Of Educational Experts (JEE), 2023)
This research is motivated by the issues of the low-level discipline of tenth-grade students of PH 2 SMK Binawisata Lembang. The problem in this research was solved by implementing football learning with the TGfU learning model. It aimed to find out to what extent the movement task of football learning could improve student discipline. This research used the classroom action research method for the tenth-grade students of PH 2 SMK Binawisata Lembang. The results of the action research showed that there was an increase in student discipline. The increase in initial value percentages is 44%. After conducting the action one-cycle one, the student’s disciplinary behavior improved to 53%. And the percentage value increased to 60% after treatment was given in action two-cycle one. In action one-cycle two, the percentage value went up to 68%. And the final value’s percentage rose to 77%. This suggests that learning tasks from football games could improve the disciplinary behavior of the student.